Deficiency of MicroRNA-181a Results in Transcriptome-Wide Cell-Specific Changes in the Kidney and Increases Blood Pressure. Issue 5 (20th September 2021) - Paterson, Madeleine R.; Jackson, Kristy L.; Dona, Malathi S.I.; Farrugia, Gabriella E.; Visniauskas, Bruna; Watson, Anna M.D.; Johnson, Chad; Prieto, Minolfa C.; Evans, Roger G.; Charchar, Fadi J.; Pinto, Alexander R.; Marques, Francine Z.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : MicroRNA miR-181a is downregulated in the kidneys of hypertensive patients and hypertensive mice. In vitro, miR-181a is a posttranslational inhibitor of renin expression, but pleiotropic mechanisms by which miR-181a may influence blood pressure (BP) are unknown. Here, we determined whether deletion of miR-181a/b-1 in vivo changes BP and the molecular mechanisms involved at the single-cell level. We developed a KO (knockout) mouse model lacking miR-181a/b-1 genes using CRISPR/Cas9 technology. Radiotelemetry probes were implanted in 12-week-old C57BL/6J WT (wild type) and miR-181a/b-1 KO mice. Systolic and diastolic BP were 4- to 5-mm Hg higher in KO compared with WT mice over 24 hours ( P <0.01). Compared with WT mice, renal renin was higher in the juxtaglomerular cells of KO mice. BP was similar in WT mice on a high- (3.1%) versus low- (0.3%) sodium diet (+0.4±0.8 mm Hg), but KO mice showed salt sensitivity (+3.3±0.8 mm Hg; P <0.001). Since microRNAs can target several mRNAs simultaneously, we performed single-nuclei RNA sequencing in 6699 renal cells. We identified 12 distinct types of renal cells, all of which had genes that were dysregulated. This included genes involved in renal fibrosis and inflammation such as Stat4, Col4a1, Cd81, Flt3l, Cxcl16, and Smad4 . We observed upregulation of pathways related to the immune system, inflammatory response, reactive oxygen species, and nerve development, consistent with higher tyrosine hydroxylase in the kidney. In conclusion, downregulation of the miR-181a gene led to increased BP and salt sensitivity in mice. This is likely due to an increase in renin expression in juxtaglomerular cells, as well as microRNA-driven pleiotropic effects impacting renal pathways associated with hypertension.